Game Theory Analysis of Business Strategies in the Coffee Shop Industry - Ratna Ekawati; Prasetyo Yulianto; Supartini Supartini; Agam Mulyanto; Abdurrochim Abdurrochim (Journal of Systems Engineering and Management, 2026)
This study aims to analyze the competition between two cafe brands from the consumer perspective. The cafe industry has experienced significant growth in recent years, with cafe brands F and C becoming quite popular. Game theory analysis was used to determine the appropriate business strategy. To prepare the model and identify consumer preferences, a survey was conducted by distributing questionnaires to 40 respondents who had experience shopping at both cafes. The results were then used to calculate the value of each strategy using the game theory model. The saddle point value obtained was 1.0. A change in strategy by one of the players would alter the game theory, so it had to be resolved with a mixed strategy with a game value of 0.9, which resulted in the right strategy for Cafe F and Cafe C.